Hydroxychloroquine Alleviates EAU by Inhibiting Uveitogenic T Cells and Ameliorating Retinal Vascular Endothelial Cells Dysfunction - Hu, Yunwei; Li, Zuoyi; Chen, Guanyu; Li, Zhuang; Huang, Jun; Huang, Haixiang; Xie, Yanyan; Chen, Qian; Zhu, Wenjie; Wang, Minzhen; Chen, Jianping; Su, Wenru; et al. (Frontiers in Immunology, 2022)
Purpose Inflammation triggers the activation of CD4+T cells and the breakdown of blood–retinal barrier, thus contributing to the pathology of experimental autoimmune uveitis (EAU). We explored the anti-inflammatory effect of hydroxychloroquine (HCQ) on EAU and the potential mechanisms active in T cells and retinal vascular endothelial cells (RVECs). Methods C57BL/6J mice were immunized with interphotoreceptor retinoid binding protein 1-20 (IRBP1–20) to induce EAU and then treated with the vehicle or HCQ (100 mg/kg/day). On day 7, 14, 21, 30 and 60 after immunization, clinical scores were evaluated. On day 14, histopathological scores were assessed, and retinas, spleens, and lymph nodes were collected for quantitative polymerase chain reaction or flow cytometry analysis. RVEC dysfunction was induced by tumor necrosis factor α (TNF-α) stimulation. The expression of cytokines, chemokines, adhesion molecules, and lectin-like oxidized LDL receptor-1 (LOX-1)/nuclear factor κB (NF-κB) was measured in RVECs with or without HCQ. Results HCQ treatment protected mice from uveitis, evidenced by reduced expression of inflammatory factors, chemokines, and adhesion molecules in the retina. In systemic immune response, HCQ inhibited the activation of naïve CD4+T cells and frequencies of T effector cells, and promoted T regulatory cells. HCQ decreased IRBP1-20–specific T cell responses and proliferation of CD4+T cells in vitro. Further studies established that TNF-α induced RVECs to express inflammatory cytokines, chemokines, and adhesion molecules, whereas HCQ alleviated the alterations via the LOX-1/NF-κB pathways. Conclusions HCQ alleviates EAU by regulating the Teff/Treg balance and ameliorating RVECs dysfunction via the LOX-1/NF-κB axis. HCQ may be a promising therapeutic candidate for uveitis.